Human heterophilic antibodies against equine immunoglobulins: assessment of their role in the early adverse reactions to antivenom administration - León Montero, Guillermo (2008)
The presence of human heterophilic antibodies against horse immunoglobulins (HHA-HI) was determined by ELISA in sera from healthy volunteers and from patients who received equine antivenom for therapy of snake bite envenoming. These patients were selected from two independent clinical studies: one in Colombia in which patients received antivenom constituted by whole IgG (n = 25); and the other in Brazil where an antivenom constituted by F(ab )2 fragments was administered (n = 31). Results show that healthy volunteers have antibodies, mainly of the IgG class, able to react with whole equine IgG. Additionally, patients have IgG antibodies that react both with whole equine IgG and F(ab )2 fragments. In both clinical studies, no significant differences were observed in the HHA-HI titres between the patients who presented early adverse (anaphylactoid) reactions and those who did not develop them. In addition, no variation in titre was observed in samples collected before and after antivenom administration. These results do not support the hypothesis that the incidence of early adverse reactions to antivenom administration correlates with the titre of HHA-HI in the serum of patients. Nevertheless, participation of these antibodies as part of a multifactorial pathogenic mechanism associated with these reactions cannot be ruled out.